TOWARD A CLEANER WHITE(NESS): NEW RACIAL IDENTITIES. - INGRAM, DAVID (Philosophical Forum)
Discusses whiteness as a racial identity. Conception of new ethnicities; Image of whiteness as a racial legacy; Antiracist identity.